Empathy deficits and adolescent sexual offending: A systematic review of the evidence base. (September 2017) - Baly, Andrew; Butler, Stephen
Abstract: Although empathy deficits are commonly assumed to contribute to adolescent sex offending, no systematic review of the evidence base has been undertaken. To rectify this omission, this review examines whether current evidence supports the existence of a relationship between empathy and adolescent sexual offending. A systematic search of the evidence base found sixteen relevant empirical studies, which provided evidence that was inconclusive or subject to methodological limitations. The review suggests that further systematic and methodologically-sound research is required to determine the extent and nature of the relationship between empathy and adolescent sex offending, that any relationship between the two is unlikely to be straightforward, and that explanations of the mechanisms involved should be integrated into wider multifactorial explanations for this behavior. Highlights: We reviewed 16 studies examining empathy and adolescent sexual offending. Methodological limitations of these studies are discussed. A relationship between empathy and adolescent sex offending is not confirmed. Further systematic and methodologically-sound research is recommended.